Evaluation of pharmacological alternatives to reduce the pain and discomfort produced by electroejaculation in rams - da Silva, Mariana Karla Francolino; de Almeida Gélio, Leonardo; Oba, Eunice [UNESP]; de Freitas, Douglas Anderson; Green, Renata Elisa; Nichi, Marcílio; Crespilho, André Maciel (Wiley, 2024)
Electroejaculation (EE) represents the main technique for semen collection from domestic and wild animals independently of libido. However, the technique is associated with intense involuntary muscle contractions, vocalization, ataxia and lying down, caused by the electric stimulation of the nerves in the caudal epigastric region. These clinical manifestations represent important indicators of discomfort. In this context, the objective of this study was to evaluate two protocols of local anaesthetic blockade and two anatomical access for pharmacological desensitization of the caudal epigastric innervation as alternatives to promote comfort and reduce stress associated with EE in rams. For the study, four clinically healthy Dorper rams were selected. All animals were subjected to a design consisting of five semen collection treatments (n = 3 collections per treatment): T1—control, conventional EE without local anaesthetic blockade; T2, EE with ventral blockade (VB) of epigastric innervation using lidocaine hydrochloride 2%; T3, EE with VB of epigastric innervation using a combination of lidocaine hydrochloride 2% and fentanyl citrate; T4, EE with blockade of epigastric innervation through the perineal access using lidocaine hydrochloride 2%; T5, EE with blockade of epigastric innervation through the perineal access using a combination of lidocaine hydrochloride and fentanyl citrate. Seminal samples resulting from EE were subjectively evaluated for sperm motility and concentration, vigour and volume. Additionally, blood serum samples were collected for quantification of cortisol and creatine kinase (CK) enzyme. Assessments of stress and discomfort were conducted by measuring blood pressure, heart rate (HR) and respiratory rate (RR), as well as observing involuntary muscle contractions, ataxia and animal vocalization. No variations in blood pressure, sperm motility, vigour, CK, and cortisol were observed among the treatments. Individual variations were observed for the occurrence of vocalization (p =.0066), but there were no differences between the groups. Anaesthetic blockades conducted using the combination of lidocaine and fentanyl resulted in a lower incidence of ataxia during EE (p <.0001). It is concluded that the combination of fentanyl citrate and lidocaine hydrochloride results in less discomfort for animals undergoing EE, regardless of the anatomical access used for local anaesthetic blockades.
Keywords: anaesthetic blockade; creatine kinase; semen collection; stress; welfare